Placental Chorioangioma (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction :Placental Neoplasms are classified in to two categories based on their origin: Trophoblastic and non trophoblastic. Non trophoblastic tumors are common and benign ones include chorioangioma and teratoma. Chorioangioma of placenta is the commonest benign tumor of the placenta. It consists of a benign angioma arising from the chorionic tissue. It has been found to be associated with many serious complications such as nonimmune hydrops, congenital abnormalities, hemolytic anemia, polyhydramnios, IUGR, and IUFD. Methods: A 21 years old pregnant female 2nd gravida with 32 weeks of gestation presented to Ob/Gy department at L.G. Hospital with complaints of abdominal distension for 2 weeks associated with lower abdominal pain for 2 days. She had a history of one full term normal delivery without significant peripartum events. General examination was unremarkable. P/A was grossly enlarged with Fundal height more than gestational age, fetal heart rate was 144 /min. Per vaginal examination revealed 2 cm dilated and early effaced cervix with intact membrane. USG revealed a single live fetus with 32 weeks of gestation and without structural malformations and hydrops AFI of 42 cm hyperechoic mass of 8.5 *6.5cm on placental surface, near cord insertion with hypervascularity, separate from placental tissue suggestive of placental chorioangioma. Estimated fetal weight was 1.6kg. After a course of dexamethasone, therapeutic amniocentesis was done; She developed gross polyhydramnios after 4 days of amniocentesis followed by spontaneous preterm normal labor and delivered 1.7kg live baby without peripartum complications. Histopathological analysis of the mass revealed proliferation of capillary sized vascular channels with endothelial cells, hemorrhagic and focal area of calcifications. The neonate was admitted to NICU and was discharged after a week without complications.  Conclusion :This case illustrates the prompt and accurate diagnosis of placental chorioangioma can help apply timely interventions improving patient outcome.
Keywords: placental chorioangioma